(untitled) (Journal of Laboratory Animal Science, 2021)
The domestic fowl (Gallus gallus domesticus) is a popular commercial species and is much studied for meat and egg production. Frequent studies on genetics, immunology, diagnostics and therapeutics are conducted in this species. For all these studies frequent blood collection is required. In the present study, blood collection technique in domestic fowl was standardized, wherein a single individual researcher can restrain the bird using the weak hand in the state of tonic immobility and carry out blood collection using the dominant hand, thus precluding the need for additional manpower which enhances the efficiency of collection especially for studies involving large number of birds without exposing them to much stress and discomfort. This fulfils one of the important objectives of refining experimentation by reducing stress on the birds.